2017
DOI: 10.3390/v9060157
|View full text |Cite
|
Sign up to set email alerts
|

Rab33B Controls Hepatitis B Virus Assembly by Regulating Core Membrane Association and Nucleocapsid Processing

Abstract: Many viruses take advantage of cellular trafficking machineries to assemble and release new infectious particles. Using RNA interference (RNAi), we demonstrate that the Golgi/autophagosome-associated Rab33B is required for hepatitis B virus (HBV) propagation in hepatoma cell lines. While Rab33B is dispensable for the secretion of HBV subviral envelope particles, its knockdown reduced the virus yield to 20% and inhibited nucleocapsid (NC) formation and/or NC trafficking. The overexpression of a GDP-restricted R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 54 publications
(113 reference statements)
0
24
1
Order By: Relevance
“…If another screening method detecting only HBV particles with envelope using anti-HBs antibody were used, the result might be different. A previous study showed that Rab33B controls HBV assembly by regulating formation and/or transport of nucleocapsids (29). The study showed that knockdown of Rab33B reduced the amount of Dane particles, whereas the screening of the present study indicated that Rab33B knockdown did not affect the amount of HBV DNA but increased HBsAg in the culture supernatant.…”
Section: Discussioncontrasting
confidence: 54%
“…If another screening method detecting only HBV particles with envelope using anti-HBs antibody were used, the result might be different. A previous study showed that Rab33B controls HBV assembly by regulating formation and/or transport of nucleocapsids (29). The study showed that knockdown of Rab33B reduced the amount of Dane particles, whereas the screening of the present study indicated that Rab33B knockdown did not affect the amount of HBV DNA but increased HBsAg in the culture supernatant.…”
Section: Discussioncontrasting
confidence: 54%
“…We thus hypothesize that HBV may co-opt the Atg5-12/16L1 conjugate in a phagophore-tethered state. As supportive evidence, we recently showed that the Rab33B GTPase, an effector of the Atg5-12/16L1 conjugate, is a positive regulator of HBV assembly, guiding NC assembly/stability (26,50). Like all Rab proteins, Rab33B exerts its function in a membrane-tethered form and had been implicated in the regulation of autophagy via fusion of Rab33B-decorated, Golgi apparatus-derived vesicles with the Atg5-12/16L1 complex in order to supply lipids for the expanding phagophore (50).…”
Section: Discussionmentioning
confidence: 68%
“…Our results pose the question of whether HBV may use the Atg5-12/16L1 conjugate in a noncanonical manner (i.e., as a distinct function mediated by individual Atg proteins) or a canonical (i.e., autophagy-like) manner, with the latter involving autophagic membranes. Previously, we showed that the HBV core is able to associate with intracellular membranes (26), albeit the functional relevance is yet unknown. In the case of many other viruses, like retroviruses, membrane targeting of viral components helps to concentrate and drive the assembly reaction (47).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations